Impact of Perioperative Blood Transfusion on Postoperative Complications and Prognosis of Gastric Adenocarcinoma Patients with Different Preoperative Hemoglobin Value - Lian Xue; Xiao-Long Chen; Zhang Wei-Han; Kun Yang; Xin-Zu Chen; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Jian-Kun Hu (Gastroenterology Research and Practice)
Background. The impact of perioperative blood transfusion on the prognosis of gastric adenocarcinoma patients is still controversial. The aim of this study was to elucidate the impact of perioperative blood transfusion on postoperative complications and prognosis of patients who underwent gastrectomy for gastric adenocarcinoma with different levels of preoperative hemoglobin value (POHb). Method. From 2003 to 2011, 1199 patients who underwent curative gastrectomy were retrospectively enrolled and followed up to December 2014. Clinicopathological features and survival outcomes were compared between transfused and nontransfused patients. Results. In this study, transfused patients had more postoperative complications than nontransfused ones (P=0.002). In survival analysis, the difference was not significant between transfused and nontransfused patients with POHb between 70 and 100 g/L (P=0.191). However, in patients with POHb >100 g/L, transfused patients had significantly worse prognosis (P<0.001), especially in TNM III stage patients (P=0.002). And intraoperative blood transfusion predicted poor prognosis (P=0.001). Conclusion. Perioperative blood transfusion might lead to poor survival in gastric adenocarcinoma patients with POHb >100 g/L and transfused patients had more postoperative complications; thus it is better to refrain from unnecessary perioperative blood transfusion especially intraoperative transfusion.